Evaluation of Odontogenic Tumors Frequency in Biopsies Sent to Isfahan, Shiraz and Yazd Dental Schools - Seyed Mohammad Razavi; Nafiseh Tadayon; Seyed Hosein Tabatabaei; Zohreh Jaafari-Ashkavandi; Laleh Maleki (Isfahan University of Medical Sciences, 2022)
Odontogenic cysts and tumors are lesions found in the upper and lower jaw and oral soft tissue. The understanding and correct diagnosis of odontogenic tumors is essential because they can be invasive or recurrent in nature and evenrarely show malignant changes. The aim of this study was to evaluate the frequency of odontogenic tumors in Isfahan, Shiraz and Yazd cites.Materials & Methods:This is a cross-sectional descriptive-analytical study that was performed in the mentioned centers. The records of registered samples from the first year of establishment to 2018 have been reviewed which is approximately 18,000 cases. Samples data were extracted and recorded based on sex, age, jaw and location of involvement in affected jaw. Data were analyzed using descriptive statistics and Chi-square test (p value < 0.05).Results:In this study, a total of 498 odontogenic tumors were evaluated. The number of odontogenic tumors in Isfahan, Shiraz and Yazd cities was 313, 130 and 55, respectively. The mean age of the patients was 30.1 ± 15.9 and most of the patients were in the age group of 20 to 40 years and 53.4% were female. The most common sites of involvement were the right mandibular (29.1%) and then the left mandibular (28.3%) and the most common tumor was ameloblastoma (50.2%) and then complex odontoma (16.7%).Conclusion:Due to the frequency observed for odontogenic tumors, understanding the clinical and pathologic features of these lesions is essential for rapid and appropriate diagnosis and treatment.